The Effectiveness of Guided Inquiry-Based of Interactive Media to Increase Interests and Learning Outcomes (Universitas Negeri Semarang, 2020)
This study was based on students' low interest in learning. The renewal of learning is needed to improve students' interest and scientific literacy. The purpose of this study was to examine and analyze the effectiveness of the guided inquiry-based of interactive media to increase interest and student learning outcomes. The method used in this research was true experimental design with a form of pre-test and post-test control group design. Population in this study were students of Elementary School Pati Kidul 01. Meanwhile, sample in this study was 88 students that consists of 30 students VA as a trial class, 28 students VB as an experimental class, and 29 students VD as a control class. Student learning interest data were collected using questionnaire and analysis technique used the T test. Simultaneously, Student learning outcomes data were collected using performance tests and analyzed using the effect size and descriptive statistics. The results in this study show that guided inquiry-based of interactive media effectively increases student interest in learning as well as their science learning outcomes. It can be concluded that research on guided inquiry model which was applied to the development of interactive media has been able to increase student interest and science learning outcomes.